Pengaruh Student-Teacher Trust Terhadap Student Well-Being di SMKN X Kota Bekasi - Wijaya, Catherine Putri; Fitriani, Yulia; Pertiwi, Yuarini Wahyu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aimed to determine whether there is an influence of student-teacher trust on student well-being at SMKN X Kota Bekasi. This research employed a quantitative method. A total of 121 tenth-grade students from SMKN X Kota Bekasi participated as respondents, using probability sampling with cluster sampling as the sampling technique. The measurement tools used in this study were the student well-being scale and the student-teacher trust scale, with data collected using a Likert scale distributed via Google Form. The correlation results showed that student-teacher trust and student well-being were positively correlated with a coefficient of 0.481. The normality test indicated a significance value of p > 0.05, meaning the data were normally distributed. The linear regression test yielded a significant result with a p-value < .001, thus the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It was concluded that student-teacher trust has an influence on student well-being among tenth-grade students at SMKN X Kota Bekasi.